Law No. 3 Of The Year 2017 Amending Certain Provisions of Law No. 79 of the year 1975 Promulgating the Social Insurance Law, Law No. 99 of the year 1992, Concerning Students’ Health Insurance System, Decree-Law No. 86 of the year 2012 Regarding Preschool Children Health Insurance System, And the Value-Added Tax Law Promulgated by Law No. 67 of the Year 2016 = قانون رقم 3 لسنة 2017 بتعديل بعض أحكام القانون رقم 79 لسنة 1975 بإصدار قانون التأمين الإجتماعى، والقانون رقم 99 لسنة 1992 فى شأن نظام التأمين الصحى على الطلاب، والمرسوم بقانون رقم 86 لسنة 2012 بشأن نظام التأمين الصحى على الأطفال دون السن المدرسى، وقانون الضريبة على القيمة المضافة الصادر بالقانون رق م67 لسنة 2016 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic